2016
DOI: 10.1097/aog.0000000000001447
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Analgesia During Labor and Delivery Between 16 0/7 and 22 6/7 Weeks of Gestation

Abstract: Pain during induction of labor at previable gestational ages may be greater than is commonly appreciated. Neuraxial analgesia may provide more optimal pain relief for patients with higher estimated gestational age and fetal weight, particularly after 22 weeks of estimated gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A study on Knowledge, Attitude, and Practices of labor analgesia amongst healthcare workers showed that 43.7% felt that pain relief should be administered, 14.1% believed analgesia had adverse effects on the fetus and 11.3% reported increased risk of cesarean section [ 16 , 21 ], in contrary Neuraxial analgesia in early labor did not increase the rate of cesarean delivery, and it provided better analgesia and resulted in a shorter duration of labor than systemic analgesia [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study on Knowledge, Attitude, and Practices of labor analgesia amongst healthcare workers showed that 43.7% felt that pain relief should be administered, 14.1% believed analgesia had adverse effects on the fetus and 11.3% reported increased risk of cesarean section [ 16 , 21 ], in contrary Neuraxial analgesia in early labor did not increase the rate of cesarean delivery, and it provided better analgesia and resulted in a shorter duration of labor than systemic analgesia [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intelligent delivery room management system includes all living facilities and medical safety equipment, so that the parturient can feel warm during delivery and help the parturient to reduce the pain and stress reaction caused by negative emotions during delivery [ 18 ], prevent postpartum depression, and then reduce the risk of uterine weakness and prolonged labor, reduce the risk of neonatal asphyxia, and increase the natural birth rate. Because the medical equipment in use has safety risks, risk identification, risk assessment, and risk control are required [ 19 ]; the application quality evaluation of the analgesia pump should be strengthened in order to ensure the accuracy and reliability of the data collection of the intelligent delivery room management system [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there were few studies on the application of epidural analgesia technology in the second-trimester induced labor, and the optimal analgesic mode for the second-trimester induced labor had not been determined. [8][9][10][11] Based on the particularity of labor induction in the second trimester, and referring to the painless delivery of full-term pregnancy, we boldly tried to use epidural analgesia technology in the second-trimester induced labor, and set the analgesia time point in the cervical canal regression 60% to 70%.…”
Section: Discussionmentioning
confidence: 99%